PENGEMBANGAN SISTEM PEMERIKSAAN DOKUMEN KAPAL TIBA (Si-PDKT) PADA KSOP KELAS II CIREBON - Mustain, Iing; Herlina, Yeyen; Suswati, Elis; Wiyandi, Eko; Sarim, Sarim; Juanto, Rudi (Politeknik Bumi Akpelni, 2023)
Arriving Vessel Document Inspection System (Si-PDKT) is a web-based application that is implemented by utilizing information technology as a supporting tool for optimizing memorandum services in the process of inspecting arriving ship documents at the Class II Cirebon Harbormaster and Port Authority Office. The purpose of developing the Si-PDKT application that will be implemented in KSOP Class II Cirebon Section Legal Status and Ship Certification is more efficient management of ship data, digitally stored ship documents, avoiding document loss, facilitating the management of ship transactions, conducting validation and verification quickly . The method used is development research. In development research, a system design is carried out which is carried out in several stages based on an analysis of the needs of the system to be used. The stages are divided into 3 main stages, namely infrastructure requirements, system creation, and application usage. The research results show that the Si-PDKT that was built can be accessed at the address https://sipdkt.ksopcirebon.id. The stages of using Si-PDKT are 1. creating an account via email, 2. the user uploads the company decree, 3. after being verified the user changes the profile, 4. on the company data menu, the user can choose the company where he works, 5. on the ship data menu, the user can add ships, 6. on the menu data memo-in contains the ship's data along with the documents and the memo-in. 7. If it has been filled in, a memo-in history will appear. At the end of verification from the operator, a verification status will appear where there is a color change following the verification status, and if you click on verification, the verification history will appear. If it has been verified as final, then the Memo In document can be downloaded